Analysis of Disaster Risk Management in Colombia : A Contribution to the Creation of Public Policies - Campos Garcia, Ana; Holm-Nielsen, Niels; Diaz G., Carolina; Rubiano Vargas, Diana Marcela; Costa P., Carlos R.; Ramirez Cortes, Fernando; Dickson, Eric (Washington, DC: World Bank, 2013)
The objective of this analysis is to assess the state of progress of risk management in Colombia and propose recommendations to help the Government set public policy in the short-and long-term. For this reason, the study sought to: (i) establish the risk and impact of disasters in recent decades, (ii) identify legal, institutional and conceptual themes in the country, (iii) review the state and evolution of investment in risk management, (iv) analyze the role of local authorities and industry in the risk management, and (v) identify gaps and challenges in the definition of the responsibilities of public and private sectors. This report, a product of joint work with multiple public and private agencies, is not limited in analyzing the causes of risk and measuring their growth. By contrast, it elaborates on the institutional developments in the risk management at different levels of government and how the topic is incorporated in the territory of public administration and industry. It further states the great opportunities for joint risk management instruments of disaster planning, investment, existing monitoring and control, and shows the need to define public and private responsibility as part of a reduction strategy of the state's fiscal vulnerability. In conclusion, the study shows that if the country does not want to see economic growth accompanied by more frequent and larger losses it will be essential to have a radical change in development policies and land management practices and industry. Therefore, the present document defines a set of recommendations to improve management of disaster risk at the level of state policy, showing that the priority to reduce the impact of disasters is based on the task of improving conditions of use and occupation of territory.